Principles of employing foreign workers – examples of labor law violations - Skałka, Michał (The use of atypical forms of employment in violation of labour and social security laws - diagnosis and prospects for the future, 2023)
This article examines the principles of employing foreign workers in the Polish and European labor markets, identifying violations of labor law. The regulations regarding the legalization of employment, flexible forms of engaging foreign workers, and the enforcement of labor rights are discussed. Special attention is given to examples of unfair practices by employers and temporary employment agencies, along with the consequences of violations. The article emphasizes the role of supervisory institutions and non-governmental organizations in safeguarding the rights of foreign workers.